2007
DOI: 10.1111/j.0014-3820.2001.tb00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Holarctic Phylogeography of Arctic Charr (Salvelinus Alpinus L.) Inferred From Mitochondrial Dna Sequences

Abstract: This study evaluated mitochondrial DNA (mtDNA) sequence variation in a 552-bp fragment of the control region of Arctic charr (Salvelinus alpinus) by analyzing 159 individuals from 83 populations throughout the entire range of the complex. A total of 89 (16.1%) nucleotide positions were polymorphic, and these defined 63 haplotypes. Phylogenetic analyses supported the monophyly of the complex and assigned the observed haplotypes to five geographic regions that may be associated with different glacial refugia. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
241
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(269 citation statements)
references
References 66 publications
23
241
5
Order By: Relevance
“…Attempts to detect the genetic differentiation between sympatric morphotypes of lacustrine charrs, including those with different trophic specialization, on the basis of the mtDNA variability analysis (Danzmann et al, 1991;Brunner et al, 1998Brunner et al, , 2001Salmenkova et al, 2005;Radchenko et al, 2006) were mostly unsuccessful. A conclusion was made that the low resolution capability of mtDNA analysis is connected with a low general level of mtDNA diversity of charr fishes, whose historical ranges were in areas of cyclic glaciations in the Pleistocene (Brunner et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts to detect the genetic differentiation between sympatric morphotypes of lacustrine charrs, including those with different trophic specialization, on the basis of the mtDNA variability analysis (Danzmann et al, 1991;Brunner et al, 1998Brunner et al, , 2001Salmenkova et al, 2005;Radchenko et al, 2006) were mostly unsuccessful. A conclusion was made that the low resolution capability of mtDNA analysis is connected with a low general level of mtDNA diversity of charr fishes, whose historical ranges were in areas of cyclic glaciations in the Pleistocene (Brunner et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A conclusion was made that the low resolution capability of mtDNA analysis is connected with a low general level of mtDNA diversity of charr fishes, whose historical ranges were in areas of cyclic glaciations in the Pleistocene (Brunner et al, 2001). Salmenkova et al (2005) have shown that charrs of the Lake Kronotskoye basin are differentiated at allozyme loci and reliably (P \ 0.001) differ in the total estimate of five microsatellite loci.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently most of the stocked individuals were able to contribute to the established populations, since stochastic processes accompanying the founding with only a few individuals did not alter the haplotype composition (Hansen and Mensberg 1996). On the other hand, it has been shown at length for brown trout (Berrebi et al 2000a,b;Borgstro¨m et al 2002;Caudron and Champigneulle 2002;Hansen et al 2002;Heggenes et al 2002), Atlantic salmon Salmo salar (Tessier and Bernatchez, 1999), Arctic chaff Salvelinus fontinalis (Brunner et al 2001;Englbrecht et al 2002) and grayling Thymallus thymallus (Koskinen et al 2002a) that stocking is inefficient whenever an indigenous population is present.…”
Section: The Impact Of Stocking and Migration Barriersmentioning
confidence: 97%
“…Genetic studies of Arctic populations of this species have generally focused on resolving phylogeographic structure (Wilson et al 1996;Brunner et al 2001), the evolution of ecotypic and morphological variation in sympatric populations (Arbour et al 2011;Moore et al 2013b) and relationships with closely-related species (e.g., Taylor et al 2008) whereas fine-scale assessments of population structure are very rare. Those that are available for anadromous populations in this species have typically resolved weak, but usually significant, genetic differentiation (Bernatchez et al 1998) and a high degree of straying (Moore et al 2013a).…”
mentioning
confidence: 99%